Influência do lodo de esgoto na nodulação e no desenvolvimento do Caupi (Vigna unguiculata "L" Walp) - Barboza, Rafael Sá Leitão (2007)
The intense urban growth, production of domestic and industrial residues has been increased, mainly sewage sludge. This residue has high amount of pathogenic organisms and heavy metals. The viable alternative for this residue destination is its use in agriculture improving the chemical, physical and biological soil characteristics. Allied of the capacity of some plants, Leguminosae order, to carry through symbiosis with microorganisms, generically called rhizobia, which are capable of increase nitrogen uptake in soil. The present work had as objective the evaluation of different levels of sewage sludge that make possible the best interaction with fixing nitrogen bacteria in the productivity of cowpea, aiming at to maximize the agricultural production inside of the concept of sustainable development, supplying an ambiently safe destination for the solid residues with its potential in agriculture recycling. The experiment was conducted in a greenhouse of Empresa Pernambucana de Pesquisa Agropecuária (IPA), with experimental design adopted of randomized blocks (four blocks) containing five strains of Bradyrhizobium spp. (EI-6, NFB 700, BR 2001, BR 4406 and BR 3267) and sewage sludge in four different levels (0, 25, 50 and 75 Mg ∙ ha-1) including control (without inoculation of the equivalent level of sewage sludge of 0 Mg ∙ ha-1). The sewage sludge proceeding from Sewage Treatment Station from Mangueira, Recife/PE, incorporated in the soil, from IPA Experimental Station in Itapirema/PE. The cowpea, cultivar IPA 206 , used was inoculated by a bacterial suspension with 109 CFU ∙ mL-1. Plants were harvested at 45 days, to measure shoot and root dry matter (SDM and RDM), nodule fresh matter (NodFM), total nitrogen (NTR and NTS) and leghemoglobin content (LHb). The cowpea dry matter showed higher results with the equivalent level of sewage sludge of 75 Mg ∙ ha-1, however were not affected inoculated strains. This equivalent level of sewage sludge demonstrated content increment of CEC (cation exchange capacity), Ca, Mg, and Na in the soil after application. The nodule fresh matter was presented in higher quantity of equivalent level of sewage sludge 25 Mg ∙ ha-1. The strains EI-6 presented higher nodule fresh matter. The application of this residue as fertilizer and the use of the strains NFB 700 and BR 4406 showed that these treatments can be used for seeds production in cowpea